2019
DOI: 10.1016/j.radcr.2018.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing angiomatoid nodular transformation of the spleen: A case report of thrombocytopenia and a hypervascular splenic mass

Abstract: IntroductionSclerosing Angiomatoid Nodular Transformation of the spleen is a benign vascular lesion with no known etiology.Presentation of CaseWe report a new case in a symptomatic twenty-one-year old female with thrombocytopenia and a hypervascular splenic mass discovered on ultrasound. Two MRIs were performed prior to hand-assisted laparoscopic splenectomy. The specimen was sent for histopathologic analysis with confirmation of final diagnosis from an outside facility.DiscussionSclerosing Angiomatoid Nodular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…This pattern is due to central stellate fibrous stroma with fibrous septa separating angiomatoid nodules. 9,10 MRI of SANT on T2-weighted imaging show the lesion as a spoke-and-wheel pattern, which is similar to the pattern obtained by multiphase imaging with CT and may be useful for the diagnosis of SANT. 6 Pre-operative diagnosis of SANT is difficult with no specific or sensitive method available to rule out malignancy and other differential diagnosis.…”
Section: Discussionsupporting
confidence: 65%
“…This pattern is due to central stellate fibrous stroma with fibrous septa separating angiomatoid nodules. 9,10 MRI of SANT on T2-weighted imaging show the lesion as a spoke-and-wheel pattern, which is similar to the pattern obtained by multiphase imaging with CT and may be useful for the diagnosis of SANT. 6 Pre-operative diagnosis of SANT is difficult with no specific or sensitive method available to rule out malignancy and other differential diagnosis.…”
Section: Discussionsupporting
confidence: 65%
“…Other signs and symptoms that have been described in literature include pelvic or flank pain, vomiting, constitutional symptoms (such as fever, weight loss and night sweats), hematologic abnormalities (e.g. thrombocytopenia, pancytopenia and anemia) and splenomegaly [ 2 , 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SANT may be indirectly associated with other cases of malignity that have comorbidities (16%, n = 37) (colorectal cancer 2.1%, gastric cancer 2.1% and lung cancer 1.3%) as SANT was detected incidentally during the follow-up of primary malignities [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. The literature reports three cases of thrombocytopenia in patients with SANT [ 6 , 73 , 77 ]. Dieobold et al [ 6 ] reported a patient presenting with thrombocytopenia due to paramyxovirus 19.…”
Section: Discussionmentioning
confidence: 99%
“…Dieobold et al [ 6 ] reported a patient presenting with thrombocytopenia due to paramyxovirus 19. Gooch et al [ 73 ] noted that the surgical oncology consultation agreed that a splenic mass was the most likely cause of thrombocytopenia in their patient. Finally, Pelizzo et al [ 77 ] reported a case of SANT occurring in a nine-week-old female infant who was admitted with severe abdominal distension and rectal bleeding, severe anemia (Hb 4.6 g/dL), thrombocytopenia (54 × 103/μL) and coagulation abnormalities resulting from persistent abdominal hemorrhaging from ruptures of the spleen capsule that were un-responsive to blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation